Amino acid-based carbon quantum dot modified MIL-53 (Fe): Investigation of its visible-driven photocatalytic activity provided by a highly efficient photoreactor. (February 2023) - Rezaei, Hooman; Zinatizadeh, Ali Akbar; Joshaghani, Mohammad; Zinadini, Sirus
Abstract: As a promising approach to addressing the ever-increasing concern of dye contaminants, visible-driven amino acid-based carbon quantum dot/MIL-53 (Fe) binary composite with excellent photocatalytic activity and stability was successfully fabricated for the first time by solvothermal technique and employed for methylene blue (MB) photodegradation in a highly efficient photoreactor. The optimum nanocomposite was obtained by doping 3 wt % amino acid-based carbon quantum dot in toMIL-53 (Fe) pores and characterized utilizing several analyses, including XRD, FTIR, FESEM, DRS, EDX, TEM, EIS and PL to investigate its morphology, optical, and electrochemical properties. Enhanced separation of charge carriers as well as increased visible light absorption capacity of MOF particles led to a maximum photocatalytic MB removal of 98%when employing the optimum nanocompositeunder visible light exposure. Central composite design (CCD) was employed to investigate the effects of four independent variables, including catalyst loading (0.5–2.5 g/L), dye concentration (20–50 ppm), initial pH (5–11), and irradiation time (0.5–2.5 h), and optimize the MB removal efficiency of the catalyst. The results verified the deteriorating impact of increasing the dye concentration as well as decreasing the catalyst dosage, initial pH, and irradiation time on the photodegradation efficiency of the hybrid nanocomposite. The reusability results further confirmed the stability and reliability of the nanocomposite, indicating that it could be used in subsequent runs with relatively stable photocatalytic activity. Photocurrent response experiments further confirmed that the amino acid-based carbon quantum dots enhanced the separation and migration of photoinduced electrons and holes. Active species trapping studies suggested that holes (h + ) and hydroxyl radicals ( OH) were more prominent than superoxide radicals ( O 2− ) throughout the organic degradation process. Ultimately, a potential photocatalytic mechanism was proposed in light of the test results. Graphical abstract: Image 1 Highlights: The N-CQDs were imbedded in MIL-53 (Fe) through a facile method. N-CQDs integration boosted the visible-light photocatalytic activity of MIL-53 (Fe). N-CQDs serve as both electron-acceptor and light converter for efficiency increase. Design and fabrication of a highly efficient photoreactor was accomplished.